Microstructures and ion-irradiation behaviour of friction stir welded 12Cr-ODS steel. (2nd January 2018) - Guo, Y. H.; Chang, Y. Q.; Zhang, J.; Li, J. Z.; Ukai, S.; Wan, F. R.
ABSTRACT: 12Cr oxide dispersion strengthened steel was successfully joined by friction stir welding (FSW), and the joints were irradiated with 3 MeV Au ions at 500°C. The morphology of grains, dislocations, sizes and distributions of nano-sized oxide particles (NPs) in different zones of the FSW joints were analysed. It was found severe plastic deformation occurred and fine equixed grains were formed in stir zone (SZ). The NPs coarsen obviously in thermal-mechanically affected zone (TMAZ) on advancing side (AS) due to the relative movements of plastic materials with high-velocity gradient. The size distributions of the NPs in base metal (BM), heat affected zone (HAZ) and RS-TMAZ are concentrated in a smaller range than those in SZ and AS-TMAZ. Finer grains and high density of dislocations result in hardness increasing obviously in SZ. Irradiation introduced higher hardening in HAZ because of its less grain boundaries and dislocation density compared with SZ and BM.